One-step Spray coating CsPbBr3 film for planar photodetector applications - Thanh, Bui Xuan; Phuong Nam, Tran; Hoan, Tran Quoc; Tuan, Pham Van; Thanh Tung, Duong (VNU Journal of Science: Mathematics - Physics; Vol 39 No 2DO - 10.25073/2588-1124/vnumap.4795, 2023)
Metal halide perovskite, a promising semiconductor material, is suitable for new generation optoelectronic application. In comparison to organic -inorganic hybrid perovskites (OIHP), all inorganic CsPbX 3 (X = Cl, Br and I) show superior thermal and chemical stability. Although there are many kinds of coating procedures for producing perovskite QDs peorovskite film, most studies of CsPbX 3 perovskite thin film fabrication focus on solution processing techniques such as spin coating. Unfortunately, the CsPbBr 3 precusor dissolubility is very low compared to OIHP, resulting in a low materials utilization and poor uniformity for the large-scale area. In this work, we report a facile spray coating method to produce CsPbBr 3 film on pre-patterned Pt electrode for photodetector (PD) application. The spray-coated perovskite was demonstrated suitable for photodiode application with numbers figure of merit such as: A high responsivity of 60 A/W, high detectivity of 6× 10 -13 Jones, the response time (rising and fall time) below 17 ms were obtained at 1 V under 405 nm illumination. From this study, we belive that the spray deposition technique will benefit for futher thin film-based perovskite optoelectronic devices.